Analisis Risiko Operasional Bank Syariah Pada Masa Pandemi Covid-19 - Fauziah, Heftika Nur; Fakhriyah, Aini Nur; Abdurrohman, Abdurrohman (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
This study aims to determine the risk management carried out by PT.BNI Syariah KC Mataram during the COVID 19 pandemic. This study uses a qualitative method with a case study approach. The data collection technique used in this study was interviewed. The analysis technique used in this research is an explanation or explanation. The results of this study indicate that operational risk is divided into two, namely the risk to the customer and the risk to the bank, including limitation of service offices, increased operating expenses and decreased profit. The factors that cause operational risk are divided into internal factors from the bank and external factors from customers, the method used by BNI Syariah KC Mataram to overcome operational risk that occurs is to focus on these 2 factors, optimize controlling for all employees (internal) and also optimize controlling for customers (external).